Benefits and Inputs From Lactic Acid Bacteria and Their Bacteriocins as Alternatives to Antibiotic Growth Promoters During Food-Animal Production - Vieco-Saiz, Nuria; Belguesmia, Yanath; Raspoet, Ruth; Auclair, Eric; Gancel, Frédérique; Kempf, Isabelle; Drider, Djamel (Frontiers in Microbiology, 2019)
Resistance to antibiotics is escalating and threatening humans and animals worldwide. Different countries have legislated or promoted the ban of antibiotics as growth promoters in livestock and aquaculture to reduce this phenomenon. Therefore, to improve animal growth and reproduction performance and to control multiple bacterial infections, there is a potential to use probiotics as non-antibiotic growth promoters. Lactic acid bacteria (LAB) offer various advantages as potential probiotics and can be considered as alternatives to antibiotics during food-animal production. LAB are safe microorganisms with abilities to produce different inhibitory compounds such as bacteriocins, organic acids as lactic acid, hydrogen peroxide, diacetyl, and carbon dioxide. LAB can inhibit harmful microorganisms with their arsenal, or through competitive exclusion mechanism based on competition for binding sites and nutrients. LAB endowed with specific enzymatic functions (amylase, protease…) can improve nutrients acquisition as well as animal immune system stimulation. This review aimed at underlining the benefits and inputs from LAB as potential alternatives to antibiotics in poultry, pigs, ruminants, and aquaculture production.